EAACI Food Allergy and Anaphylaxis Guidelines: managing patients with food allergy in the community. Issue 8 (18th June 2014) - Muraro, A.; Agache, I.; Clark, A.; Sheikh, A.; Roberts, G.; Akdis, C. A.; Borrego, L. M.; Higgs, J.; Hourihane, J. O'B.; Jorgensen, P.; Mazon, A.; Parmigiani, D.; et al.
Abstract The European Academy of Allergy and Clinical Immunology (EAACI) Food Allergy and Anaphylaxis Guidelines, managing patients with food allergy (FA) in the community, intend to provide guidance to reduce the risk of accidental allergic reactions to foods in the community. This document is intended to meet the needs of early‐childhood and school settings as well as providers of non‐prepackaged food (e.g., restaurants, bakeries, takeaway, deli counters, and fast‐food outlets) and targets the audience of individuals with FA, their families, patient organizations, the general public, policymakers, and allergists. Food allergy is the most common trigger of anaphylaxis in the community. Providing children and caregivers with comprehensive information on food allergen avoidance and prompt recognition and management of allergic reactions are of the utmost importance. Provision of adrenaline auto‐injector devices and education on how and when to use these are essential components of a comprehensive management plan. Managing patients at risk of anaphylaxis raises many challenges, which are specific to the community. This includes the need to interact with third parties providing food (e.g., school teachers and restaurant staff) to avoid accidental exposure and to help individuals with FA to make safe and appropriate food choices. Education of individuals at risk and their families, their peers, school nurses and teachers as well as restaurant and other food retail staff can reduce the risk of severe/fatal reactions. Increased awareness among policymakers may improve decision‐making on legislation at local and national level.